The Relationship Between Self Efficacy and Family Support With Hypertension Treatment Adherence of Elderly - Ruswadi, Indra; Asyari, Hasyim; Marsono, Marsono; Akhmadi, Akhmadi; Purwanta, Purwanta (Jurnal Pendidikan Keperawatan Indonesia, 2023)
Hypertension is a degenerative disease that increasing in its prevalence. Hypertension requires a long enough time to its treatment, even if there are no symptoms the patients should continue taking medication. So, patients need to obey to take medication. Adherence to taking medication correlated with self-efficacy and family support. This research aims to determine the relationship between self-efficacy and family support in hypertension treatment adherence of the elderly at Widasari Health Center, Indramayu Regency. The research design is a cross-sectional study. The sample of this research was 78 elderly. The data analysis used univariate to explain independent variables such as self-efficacy and family support, the dependent variable is hypertension treatment adherence, while the bivariate was used to determine the relationship between independent variables and the dependent variable. Dependent variable using the chi-square statistical test. The result of this research showed that 61.5% of the elderly had high self-efficacy criteria, 71.8% of the elderly received their family support, and 60.3% of the elderly obey to hypertension treatment adherence. The chi-square statistical test showed that there was a relationship between self-efficacy and family support with hypertension treatment adherence and also there is a relationship between self-efficacy and the level of adherence to taking medication in people with hypertension. It is recommended to increase the elderly self-efficacy by being able to communicate with fellow elderly who are undergoing hypertension treatment and now have reduced symptoms due to treatment adherence. Nurses should be able to provide health promotion about the importance of self-efficacy and family support in increasing compliance for the elderly undergoing hypertension treatment.